Role of MRI in Evaluation of Compressive Myelopathy (GAIMS Journal of Medical Sciences, 2025)
Background: Compressive myelopathy is a critical condition that can result from various etiologies, including trauma, infection, neoplasms, and degenerative changes. MRI is considered the gold standard for assessing spinal cord compression, owing to its excellent soft tissue contrast and ability to produce multiplanar images.Objective: This study aims to evaluate the role of MRI in diagnosing and characterizing compressive myelopathy, with a focus on differentiating between extradural and intradural lesions.  Methods: A cross-sectional study was conducted on 50 patients with suspected compressive myelopathy referred to the Department of Radiodiagnosis, Gauhati Medical College & Hospital, Guwahati, Assam. MRI scans were performed using a 1.5 Tesla Siemens Avanto machine. The lesions were categorized based on location (extradural vs. intradural) and etiology (trauma, infection, neoplasms, etc.).  Results: The most common causes of compressive myelopathy was found to be infections (30%) and trauma (40%). Extradural lesions accounted for 84% of cases, while intradural lesions were less common (16%). MRI accurately identified cord compression, vertebral body destruction, and epidural soft tissue components in all cases. Trauma patients showed cord edema/contusion in 100% of cases, while infection cases demonstrated vertebral body destruction and pre/paravertebral collections in all cases. Neoplasms were predominantly intradural, with neurofibromas and meningiomas being the most common.  Conclusion: MRI is an indispensable tool for the evaluation of compressive myelopathy, providing detailed information on the location, extent, and nature of spinal cord compression.